Improving the diagnosis of prostate cancer by telomerase-positive circulating tumor cells: A prospective pilot study. (January 2022) - Yang, Zhenrong; Bai, Hongsong; Hu, Linjun; Kong, Defeng; Li, Guoliang; Zhao, Changyun; Feng, Lin; Cheng, Shujun; Shou, Jianzhong; Zhang, Wen; Zhang, Kaitai
Abstract: Background: Prostate-specific antigen (PSA) testing is limited in identifying prostate cancer (PCa) with modestly elevated PSA levels. Therefore, a robust method for the diagnosis of PCa is urgently needed. Methods: A total of 203 men with a PSA level of ≥4 ng/ml were eligible for enrollment in this study from July 2018 to May 2021, and randomly divided into a training set (n=78) and a validation set (n=125). Circulating tumor cells (CTCs) were detected using telomerase-based CTC detection (TBCD), and the diagnostic ability was evaluated using receiver operating characteristic (ROC) and logistic regression analyses. Findings: In the training set, the area under the curve (AUC) of CTCs was 0.842 with a sensitivity of 80.33% and specificity of 82.35%. In the validation set, the AUC of CTCs was 0.789, with a sensitivity of 79.31% and specificity of 81.58%. There was no significant difference between CTCs (AUC=0.793) and PSA (AUC=0.697) in the range of 4-50 ng/ml. In the ranges of 4-20 ng/ml and 4-10 ng/ml, the AUC of CTCs were 0.811 and 0.825, respectively, which were superior to the AUC of PSA (0.588 and 0.541). The sensitivity and specificity of CTCs in the three PSA groups were higher than 80%. Moreover, we further established a CTC+PSA combined model, which could significantly improve the diagnostic ability of a PSA level of '4-10 ng/ml'. Interpretation: TBCD could be a valuable method for distinguishing PCa and benign prostatic disease, especially in the PSA diagnostic gray area of '4-10 ng/ml'.